Spread of Human T-Lymphotropic Virus 1 and 2 Among Relatives of People Who Use Illicit Drugs in Northern Brazil - Oliveira-Filho, Aldemir Branco; Frade, Paula Cristina Rodrigues; Fonseca, Ricardo Roberto de Souza; Sawada, Leila; Martins, Luísa Caricio; Machado, Luiz Fernando Almeida; Vallinoto, Antonio Carlos Rosário; Ishak, Ricardo; Lemos, José Alexandre Rodrigues de; Fischer, Benedikt; Kupek, Emil (Frontiers in Microbiology, 2022)
The human T-lymphotropic virus 1 (HTLV-1) and 2 (HTLV-2) can be transmitted between humans by mechanisms associated with horizontal and vertical routes. Recently, high prevalence rates and levels of genetic diversity for HTLV-1 and HTLV-2 were detected among people who use illicit drugs (PWUDs) in the Brazilian state of Pará. None of the PWUDs with HTLV-1 or HTLV-2 were aware of their carrier condition of the retrovirus, and they ability to spread it to their family group, sexual partners, and other contacts. Thus, this study evaluated the presence of HTLV-1 and HTLV-2 in families of PWUDs in the state of Pará, in Northern Brazil. This descriptive study used convenience sampling and accessed 37 PWUDs and their respective families (n = 97) in 18 municipalities in the state of Pará, northern Brazil. All participants provided personal data and were tested for the presence of HTLV-1 and HTLV-2 using enzyme-linked immunosorbent assay and western blotting. HTLV positive samples were selected for Nested-PCR, and viral genotyping by nucleotide sequencing and phylogenetic analysis. HTLV-1 or HTLV-2 infections were detected in 15 families of PWUDs: 27 family members of PWUDs were infected with HTLV-1 (27.8%) and another 20 of them with HTLV-2 (20.6%). Subtypes 1a (subgroup A (54.5%)), 2b (20.5%) and 2c (25.0%) were detected. High horizontal (76.9%) and vertical (61.4%) transmission rates of HTLV were ascertained. Factors that facilitate the acquisition and transmission of HTLV-1 and HTLV-2 were reported by the participants, such as long-term relationships, unprotected sex, breastfeeding, and lack of knowledge about the condition of being a carrier of the retrovirus. Evidence indicates intrafamilial transmission of HTLV from PWUDs to members of their respective families. Key interventions should urgently be employed for the control and prevention of HTLV-1 and HTLV-2 to reduce the spread of this retrovirus in PWUDs and the general population in Northern Brazil and elsewhere.